Symbolic Meaning of Buka Luwur: a Historical and Cultural Study of Sunan Kudus Grave - Moh Rosyid (el Harakah: Jurnal Budaya Islam, 2022)
This article describes the symbolic meaning of Luwur (a covering cloth) of the grave of Sunan Kudus, the first preacher of Kudus in the annual tradition of Buka Luwur (replacement with new Luwur every month of Muharam/Sura). The tradition is performed by the Foundation Administrator of Mosque, Menara, and Sunan Kudus Grave (YM3SK) together with the residents of Kauman, Kudus, Central Java. The data of this study were obtained from observation, interview, and reference investigation with a qualitative descriptive analysis. The research result showed that the luwur of Sunan Kudus grave behind al-Aqsha Menara Mosque assigns various symbolic meanings. The event of Buka Luwur tradition is performed in every first to tenth of Sura/Muharam month, through the distribution of Asura porridge and jangkrik rice to the residents of Kauman village, Islamic art performance, learning about Islamic New Year (Muharram), and replacement of the old Luwur with the new one. The motif of Luwur consists of jasmine, unthuk banyu, kompol, and wiru, which symbolize honor to Sunan Kudus. The tradition has been conserved to honor the traces of dakwah of Sunan Kudus. Artikel ini menjelaskan makna simbolis dari Luwur makam Sunan Kudus, da'i pertama di Kudus dalam tradisi tahunan Buka Luwur (penggantian Luwur baru setiap bulan Muharam/Sura). Tradisi tersebut dilakukan oleh Pengurus Yayasan Masjid, Menara, dan Makam Sunan Kudus (YM3SK) bersama warga Desa Kauman, Kecamatan Kota, Kudus, Jawa Tengah. Data penelitian ini berasal dari observasi, wawancara dan investigasi referensi dengan analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Luwur makam Sunan Kudus di belakang Masjid Al-Aqsha Menara memiliki berbagai makna simbolis. Rangkaian acara tradisi Buka Luwur dilakukan setiap bulan Sura/Muharam pertama hingga kesepuluh, yaitu pembagian bubur Asura dan nasi jangkrik kepada warga desa Kauman, pertunjukan atraksi Seni Islam, program pengajaran Tahun Baru Islam (Muharram), dan penggantian Luwur lama dengan yang baru. Motif Luwur terdiri dari melati, unthuk banyu, kompol, dan wiru, yang memiliki makna simbolis penghormatan terhadap Sunan Kudus. Tradisi tersebut dilestarikan untuk menghormati jejak-jejak dakwah Sunan Kudus.